On Correct Nomenclature of Himalayan Bird Cherries - Singh, Gurcharan (Indian Forester, 1974)
The present piper relates to the nomenclature of the common Himalayan bird cherry, and its villose variety from the Eastern Himalaya The cam-non Himalayan plant, being distinct from the European bird cherry belongs to Padus cornuta (Wall. ex Royle) Carriere. A new combination P. cornuta (Wall. ex Royle) Carriere var. villosa (Hara) Singh is proposed for the villose variety from Eastern Himalayas, based oil Prunus cornuta (Wall. ex Royle) Steud. Var. villos Hara.